PENINGKATAN PEMAHAMAN KONSEP HUKUM ARCHIMEDES BERBASIS PEMBELAJARAN MODEL KOOPERATIF TIPE TWO STAY TWO STRAY - Samosir, Angelina Yusnaini; Sitompul, Stepanus Sahala; Hidayatullah, Muhammad Musa Syarif (Jurnal Inovasi Penelitian dan Pembelajaran Fisika, 2023)
This research seeks to assess how effective the implementation of the Two Stay Two Stray cooperative learning model is. This model used to improve the understanding of the concept of Archimedes' law material in class XI Mathematics and Natural Sciences Abdi Wacana Pontianak Christian High School. A quantitative approach used in this research with experimental methods. The design of research was designed using the model for Pre-Experimental Design employs a one-group pretest-posttest structure pattern. The cooperative learning model of Two Stay Two Stray type consists of six stages, namely preparation, presentation by the teacher, group activity, formalization, evaluation, and reward. In this study, the instruments used included pretest and posttest as well as questionnaires. The results showed that concept understanding before the application of this learning model was 52%, classified in the low category. After applying the model, concept understanding increased to 79%, classified in the high category, with an increase of 27% from before. Measurement using N-Gain resulted in a mean value of 0.5630, which is in the category of "moderate," and the percentage of N-Gain is about 56.3021, which is in the effective category, which is quite effective. In addition, the positive response of learners reached 82.5%, indicating good acceptance. Therefore, in summary, the utilizing the model of cooperative learning known as Two Stay Two Stray is quite effective in improving students' concept understanding.